STRATEGI KOMUNIKASI PEMASARAN DIGITAL SEKURITAS SAHAM DI MASA PANDEMI GELOMBANG II (STUDI PADA PT ERDIKHA ELIT SEKURITAS) - Alif Marino Kurnia Akbar, (2023)
The development of digital communication, especially during the second wave of the pandemic, has increased quite rapidly. But in this case, digital communication is not only used as a positive medium to communicate through digital media devices. Some negative behaviors such as fraud under the guise of investment can attack any individual who uses digital media as a communication platform. Of course, the interest in investing, especially during the second wave of the pandemic, made several companies, one of which is PT Erdikha Elit Sekuritas, a stock securities company that has been involved in the world capital market for more or less 34 years to carry out a digital marketing communication strategy as a form of education as well as channeling information about products and services. their services to get potential customers through digital media. the digital marketing communication strategy carried out by PT Erdikha Elit Sekuritas during the second wave of the pandemic was analyzed using Paul R Smith's SOSTAC model. Keywords: Digital marketing communication strategy, Covid-19 Pandemic wave II, SOSTAC Model.